2015
DOI: 10.1002/jhm.2535
|View full text |Cite
|
Sign up to set email alerts
|

Health information exchange systems and length of stay in readmissions to a different hospital

Abstract: BACKGROUND: Readmission to a different hospital than the original discharge hospital may result in breakdowns in continuity of care. In different-hospital readmissions (DHRs), continuity can be maintained when hospitals are connected through health information exchange (HIE) systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…27,28 Characteristics Similar to other studies, 2,3 the present study found no difference in age and sex between the two groups, but a higher number of previous admissions in patients who had a non-index hospital readmission. Unlike other studies, 29,30 CCI was significantly lower in the non-index readmission group, indicating that these patients had fewer comorbidities and possibly had a less complicated illness explaining the shorter LOS during their index admission. Recurrence of the illness provoking the index admission and the occurrence of complications during the index admission affected the likelihood of the patient being readmitted to the index hospital rather than to a non-index hospital.…”
Section: Discussioncontrasting
confidence: 84%
“…27,28 Characteristics Similar to other studies, 2,3 the present study found no difference in age and sex between the two groups, but a higher number of previous admissions in patients who had a non-index hospital readmission. Unlike other studies, 29,30 CCI was significantly lower in the non-index readmission group, indicating that these patients had fewer comorbidities and possibly had a less complicated illness explaining the shorter LOS during their index admission. Recurrence of the illness provoking the index admission and the occurrence of complications during the index admission affected the likelihood of the patient being readmitted to the index hospital rather than to a non-index hospital.…”
Section: Discussioncontrasting
confidence: 84%
“…Of the 969 community‐dwelling participants recruited to the HoPE‐FOR study, a subset of 758 (78%) members of Clalit was used for the current study, as data on readmissions to any general hospital were accurately and readily available from Clalit's EHR system . Of those, we excluded 199 due to the following reasons: 13 (2%) died during the hospitalization, 46 (6%) transferred to another ward, 16 (2%) were discharged to a post–acute care facility, and 124 (16%) dropped‐out from the HoPE‐FOR study during the hospitalization (due to unavailability because of intensive tests or procedures) or had missing data on the main variables, leaving a final sample of 559 participants.…”
Section: Methodsmentioning
confidence: 99%
“…16 For adult patients, when readmissions are fragmented across multiple hospitals, the readmission LOS increases, whereas efficient, cost-effective care decreases. 15,17 Likewise, data from health systems reveal that fragmentation of care for adults with chronic conditions results in increased health care costs, worsened outcomes (eg, increases in mortality), and longer intervals between health maintenance visits. 17,18 Although readmissions to different hospitals are associated with longer total LOS among adults, relatively little is known about the effect of fragmentation of care on overall LOS for hospitalized children.…”
mentioning
confidence: 99%
“…17,18 Although readmissions to different hospitals are associated with longer total LOS among adults, relatively little is known about the effect of fragmentation of care on overall LOS for hospitalized children. 15,16 Therefore, our objectives in this study were (1) to assess, nationally, the LOS and cost for 30-day readmissions in children; (2) to compare the LOS and cost between index admissions, readmissions, and for the episode of care (ie, combined index admission and readmission); and (3) to describe the impact on LOS and cost when a readmission occurs to the same versus a different hospital from that of the index admission.…”
mentioning
confidence: 99%